ANALYSIS OF THE FATE OF INDONESIA' S ECONOMY IN THE FUTURE - Dhella Amandha; Rizky Ardiansyah; M. Rifki Annabil; Midral Hadi; Rudhy Andrian; Tira Rahma Dina; Shabrina Nur Farah; Luthfiyyah Atikah; Oda Sharia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Court Developing countries tend to experience inflation, countries with inflation below 3% are still on the normal threshold for a country (stebisgm, 2015) but conversely a country with high and unstable inflation is a reflection of economic instability which results in a general and continuous increase in the level of prices for goods and services in a country and results in higher levels of poverty and unemployment. In this study we used a quantitative method using time series data from 2015 to 2021 and carried out statistical calculations using SPSS.. Results According to the study, the inflation rate is 3532 > 2306. The significance level is 0.039 <0.05, which means that inflation affects Indonesia's economic growth/gross domestic product (GDP). Even though the management of the state's economy cannot be separated from the state, including Indonesia from the countries affected by the state. However, the monetary and fiscal policies implemented in each country vary depending on economic conditions, direction and development goals to be achieved. The economic growth of a country, including Indonesia, is inseparable from the monetary and fiscal policies implemented by each country. However, monetary and fiscal policies differ from country to country Actual economic conditions, development trends and goals that can be achieved. An important function of financial management and financial management is to control inflation rates, cash flows and control additional costs in the company. The purpose of this study is to analyze the situation of the Indonesian economy for the next five years and to analyze the government's role in controlling inflation, monetary policy and fiscal policy and their impact on the economy. Macro - for economic analysis (Sutiono M.Kom., M.T.I, 2019) mi law near and far. The method used is a literature survey methodology and the data used is secondary data which is consistent with various relevant literature. To overcome inflation, monetary policy, and taxation, the government must implement performance-related macroeconomic policies. Measures of inflation and economic growth. Therefore, all countries must maintain economic stability is threatened. Inflation is one of the most important factors in the economy. The inflation rate is caused by many changes regarding major economic changes such as economic growth and unemployment. Thus, expansion is a variable that is often observed and tested both theoretically and empirically. Economic growth can only be successful if it is supported by sustainable growth, which then must improve people's welfare. Growth recovery refers to the rate at which growth returns to balance after a shock. In addition, this research examines sustainability factors in various regions in Indonesia. To measure the sustainability of inflation, this study uses the univariate autoregression (AR) model.. According to the results there are eight, namely: (1) provinces/cities in East Java experienced higher growth rates during the study period. The highest elevation is in the town of Probolingo and the lowest in the town of Madiun. The things that contribute the most to growth are made from staple foods like eggs, rice, chicken, tomatoes, beans and beef. and others (2) According to our findings, the increase in inflation in the eight provinces/districts of East Java was high enough to attract editorial attention. high inflation expectations also lead to persistent inflation. Based on this information, the government needs to formulate a strategy to control inflation that is sustainable and measurable, such as strengthening the role of groups. Regional Inflation Monitor (RPID). Unemployment and inflation are two important issues in any country. The difference between these two variables remains a subject of research among economists as evidenced by the Phillips curve theory.